Local Wisdom about Food Sustainment in the Bima Community - Qayimah, Nur; sumarwati, Sumarwati; Suryanto , Edi (Journal of World Science, 2024)
Global climate change has a direct impact on world food security, including in Indonesia. In fact, previous generations have local wisdom in the context of food preservation. The people of Bima Regency, West Nusa Tenggara Province also have local wisdom about how to maintain food that has long been inherited from their ancestors. This study aims to identify how the Bima people with their local wisdom can maintain food values ??in their area. This study was conducted using a qualitative method with an ethnographic strategy. The data sources were informants including traditional leaders, local communities, traditional ceremony implementers, and the procession of traditional ceremonies and their equipment. Sampling was carried out using purposive sampling and snowball sampling. Data collection was carried out through in-depth interviews and field observations of traditional ceremony processions. Data validity testing was carried out by triangulation of sources and methods. Data analysis techniques with interactive models. The results of the study showed that the value of local wisdom about food preservation was presented through folklore, traditional ceremony processions and traditional ceremony offerings. The folktale entitled fare ma lingi conveys the message that we must maintain agricultural activities in accordance with the teachings of our ancestors. The procession of the ampa fare traditional ceremony conveys the message of a frugal lifestyle and managing food